BENTUK PENYAJIAN DAN FUNGSI MUSIK NAGA YAYASAN PANCA BHAKTI PADA PERAYAAN CAP GO MEH - Firdaus Irawan; Yudhistira Oscar Olendo; Christianly Yery Silaban (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research is motivated by the uniqueness of the Naga performance which lies in the form of the Naga music’s presentation and function. Therefore, the researcher documents the form of presentation and the function of dragon music by writing and pictures. The method of this research was a descriptive method in the form of qualitative research and ethnomusicological approach. The techniques of data collection were observation, interviews and documentation studies. The technique of data validity testing was by extended the observations and triangulate sources. Based on the data analysis, it was concluded that the form of presentation and the function of the Dragon Music of Panca Bhakti Foundation at the Cap Go Meh Celebration in Pontianak City is traditional music played by a group of people or ensemble, consist of one Loukou player (Drum), two Chem players / Chep-chep (cymbal) and two Tang Lou players (Flat Gong). The Dragon Music on Panca Bhakti Foundation at the Cap Go Meh Celebration in Pontianak City has a function as (1) accompaniment music, (2) to entertain, , (3) a Cultural Continuity, (4) a Symbolic Function, (5) an Education Function, and (6) As a Contribution to Social Integration. Keywords: The form of Presentation and the Function, Dragon Music